The impact of Robinson's strategy on the achievement of art history students in the art history course (Journal of the College of Basic Education, 2023)
¬¬¬¬¬ Research Abstract:The study aimed at the impact of Robinson's strategy on the achievement of art history students at the Department of Art Education. To achieve the goal of the research, the researchers used the experimental design with two equal groups, the experimental and the control, with the pre and post test for the subject of art history, to suit it on a sample of students from the Department of Art Education / College of Basic Education / first stage. In order to reach the results of the research, the research tool was a knowledge achievement test for the subject of art history, the researchers analyzed the data into systematic images for their research using the statistical bag for social sciences (SPSS).The most important search results showed the following:1. The interaction process provided by this strategy increased the students' ability to memorize information and understand it correctly, in a scientific and practical way.2. The use of Robinson's strategy gave students the possibility of generating questions through the survey process and the preliminary view of the subject and the possibility of asking them in the lesson, as it generates ideas, excitement and longing for the purpose of solving the problem in a scientific and accurate manner, which results in raising students' achievement in the study.Recommendations:In light of the results and conclusions reached by the researchers, they recommend a number of recommendations, including:1- The need to use Robinson's strategy in other subjects for other stages, and to investigate its impact on students' achievement.2- Providing the necessary equipment and devices and preparing books, resources and modern teaching aids in educational institutions to facilitate the use of Robinson's strategy.Suggestions:In order to complement and develop the current research, the researchers suggested the following:1- Conducting a similar experimental study using Robinson's strategy in the subject of artistic appreciation.Keywords: effect - Robinson's strategy - art history